2014
DOI: 10.1080/01694243.2014.973158
|View full text |Cite
|
Sign up to set email alerts
|

Injection-molded plastic plate with hydrophobic surface by nanoperiodic structure applied in uniaxial direction

Abstract: The purpose of this research is to establish a processing method for a wide-area nanometer scale periodic structure on the surface of a plastic plate in order to improve its hydrophobicity. We also evaluated the effect of a nanoperiodic structure applied in the uniaxial direction. Plastic plates of acrylonitrile-ethylene-styrene with dimensions of 100 × 100 mm 2 with a nanoperiodic structure on their surfaces were fabricated using a femtosecond laser and an injection molding technique. In the injection molding… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
4
0

Year Published

2016
2016
2022
2022

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 7 publications
(6 citation statements)
references
References 29 publications
1
4
0
Order By: Relevance
“…These results showed that the water droplet did not reach the bottom of the re-entrant texture because it was sufficiently suspended to exceed the depth. It has also been reported that periodic structures applied in a uniaxial direction affect the apparent contact angles by less than 2% [34]. Our results were thus consistent with those of the previous report.…”
Section: Measurement Of Apparent Contact Angle and Sliding Characteri...supporting
confidence: 94%
“…These results showed that the water droplet did not reach the bottom of the re-entrant texture because it was sufficiently suspended to exceed the depth. It has also been reported that periodic structures applied in a uniaxial direction affect the apparent contact angles by less than 2% [34]. Our results were thus consistent with those of the previous report.…”
Section: Measurement Of Apparent Contact Angle and Sliding Characteri...supporting
confidence: 94%
“…11,[23][24][25][26][27][28][29][30][31][32] Various direct write and replication methods have been employed to micro/nanostructure bulk hydrophobic materials. Replication methods such as casting a polymer solution or melt on a template, 33,34 injection moulding, [35][36][37] hot embossing, 38,39 and sacrificial etching 7,40,41 have been utilized. Photolithography and femtosecond laser ablation have been used for structuring of the master, but both are time consuming and expensive.…”
Section: Introductionmentioning
confidence: 99%
“…In the literature, many authors correlated the hydrophobicity of a surface to its topography [ 25 , 40 ]. The presence of a hierarchical structure on a surface induces an increase of the hydrophobicity with respect to a smooth surface [ 41 ].…”
Section: Resultsmentioning
confidence: 99%
“…The latter surely presents the advantage of cheaper and faster production [ 20 , 21 , 22 , 23 , 24 ]. Yamaguchi et al [ 25 ] proposed to replicate a master having nano-periodic structures, obtained by a femtosecond laser, layered on the cavity surface. They studied the effect of nano-structures replica on the wettability of acrylonitrile-ethylene-styrene moldings and found that the apparent contact angle increases with respect to the surface obtained on a smoother cavity.…”
Section: Introductionmentioning
confidence: 99%